Peritoneal Endometriosis Impairs Ovarian Reserve and Increases Atresia in a Rat Model - Analía Ricci; Tatiana Bengochea; Carla Olivares; Sofía del Valle; Julieta Simone; Kristina Gemzell-Danielsson; Rosa Inés Barañao; Gabriela Meresman; Mariela Bilotas (Biomedicines)
Background/Objectives: Endometriosis has a marked impact on fertility, although the mechanisms behind this relationship remain poorly understood, particularly in cases without significant anatomical distortions or in the context of ovarian endometriomas. This study aimed to investigate the effect of peritoneal endometriosis on ovarian function by assessing ovarian reserve and apoptosis. Methods: Peritoneal endometriosis was surgically induced in Sprague Dawley rats through the autotransplantation of uterine fragments onto the bowel mesothelium. One month post-surgery, ovarian structures were counted, follicle and corpora lutea apoptosis was evaluated by TUNEL, and apoptotic-related protein expression in ovaries was assessed by Western blot. Additionally, a co-culture system using 12Z endometriotic and KGN granulosa cell lines was utilized to evaluate gene expression by RT-qPCR. Results: Rats with peritoneal endometriosis exhibited a significant reduction in ovarian structures characterized by a low number of total follicles, particularly primordial, primary, preantral, and late-antral follicles. Consistently, AMH protein expression was decreased in ovaries in the presence of endometriosis. In addition, this disease led to a significant increase in late-antral follicles that were TUNEL-positive and in the number of apoptotic cells in corpora lutea, indicating higher apoptosis in endometriosis ovaries. Concomitantly, the altered expression of apoptosis-related proteins was observed, with increased procaspase 3 and decreased BCL-2 expression. In addition, KGN granulosa cells co-cultured with 12Z endometriotic cells displayed reduced KITLG mRNA expression and increased AMHR2 mRNA expression. Conclusions: Peritoneal endometriosis significantly impairs ovarian health by disrupting folliculogenesis, reducing ovarian reserve, and increasing apoptosis, potentially accelerating ovarian aging and contributing to infertility. These results underscore the need for further research to identify the molecular pathways involved and to develop targeted therapeutic strategies.